Simulation study on optimization of smoke control and exhaust strategies for networked underground tunnel groups - Ruinan AN; Peng LIN; Yong XIA; Xin Wang; Weifeng ZHANG; Chao ZHANG; Shuai ZHANG (Meitan xuebao)
Smoke control in the complex structure of network-type giant underground tunnels is a difficult problem. Due to the multiple and random fire causes, high temperature of smoke gathering at the top of the enclosed space, multipath rapid propagation, and disorganization of the ventilation system due to the smoke flows, the fire condition is expanded accidentally. A full-scale model of the giant underground tunnel group was developed, and simulation studies were carried out to characterize the smoke propagation and temperature distribution under three typical strategies of natural smoke dissipation in a shaft, exhausted smoke by mechanical ventilation, and blocked smoke by smoke barriers. The smoke propagation is divided into promotion and suppression areas to analyze the effect of smoke control and extraction, and the conclusions of the smoke control and safe rescue design are as follows: ① under the strategy of natural smoke dissipation in shaft, the smoke spread is directly related to the cross-section of the tunnel, and the smoke mainly spreads along the hydraulic tunnels. The stratification of smoke and air in the non-shaft area is obvious, high-temperature smoke spreads steadily along the top, and the low-temperature fresh air in the middle and lower parts of the shaft is transmitted to the location of the fire source to replenish, and the stratification of smoke and air in the shaft area is destroyed, and the degree of smoke entrainment is increased, and the temperature is lowered. The area near the shaft has a certain smoke evacuation capacity, and the overall capacity of smoke control is very weak. ② under the strategy of the ventilation-based smoke exhaust, the smoke is mainly exhausted in shaft. The path of smoke exhaust from ventilation and shafts is the same, with the characteristic of coupling to enhance the smoke exhaust capacity. The height of the smoke layer in the upstream area of the fire increased, most of the smoke propagated downwind, the temperature inside the shaft increased, and a “low-temperature zone” appeared at rear of the shaft. The propagation ability of the smoke suppression zone along the hydraulic tunnels is weakened, and the overall capacity of smoke control is improved. ③ Under the strategy of smoke exhaust by ventilation and smoke barrier, the smoke propagation is delayed, and in the single-tunnel spreading stage, the characteristic of smoke propagation mainly along hydraulic tunnels is changed, and the overall controllability of the smoke at this stage is strong; in the stage of smoke network is not connected, there is a strong smoke reversal phenomenon, the coupling control effect of shaft and smoke barrier significantly weakened the smoke spread intensity in the region of smoke spread suppression area downwind of the fire source, the overall capacity of smoke control is relatively high; in the stage of the smoke network has been connected, the effect of the smoke barrier is not obvious, but the enhancement of the mechanical ventilation speed directly weakens the ability of the smoke to spread to the upstream hydraulic tunnel through the construction branches, and the overall capacity of smoke control is general. In the design of safety rescue path, area of smoke spread promotion area downwind of the fire source is the main path of shaft and ventilation smoke exhaust. The main and side passages of the construction branch are the pathways for people and smoke spreading respectively, and escape via a connecting tunnel to hydraulic tunnels far from the fire. The results of this study provide a reference for similar projects in smoke control and safety rescue.